2014
DOI: 10.3852/13-344
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of Serpula lacrymans in Europe with an outlook to the French population

Abstract: In this study the genetic variation and population structure in a French population of the dry rot fungus S. lacrymans was investigated using 14 microsatellites markers and compared to the rest of Europe. In that comparison the French population possessed the same allelic diversity as rest of Europe. A weak geographic structuring of the genetic variation was observed across Europe, where the French isolates to some extent separated from the rest of Europe, indicating that weak barriers to gene flow exists. Eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…lacrymans still allows 25% of the spores from the same fruit body to mate. No putative clonal isolates were found in our or previous studies (Engh, Skrede et al, 2010; Kauserud et al, 2007; Maurice et al, 2014), supporting that selfing or clonal dispersal is not the main explanation of the slow linkage decay.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…lacrymans still allows 25% of the spores from the same fruit body to mate. No putative clonal isolates were found in our or previous studies (Engh, Skrede et al, 2010; Kauserud et al, 2007; Maurice et al, 2014), supporting that selfing or clonal dispersal is not the main explanation of the slow linkage decay.…”
Section: Discussionsupporting
confidence: 78%
“…Previous population genetic studies based on microsatellites showed that the genetic diversity of the European population is very low (Engh et al, 2010; Kauserud et al, 2007; Maurice et al, 2014), suggesting that a few individuals established through a founder event. Further evidence for a narrow population bottleneck in Europe stems from a limited number of mating type (MAT) and self‐recognition vegetative incompatibility ( vic ) alleles present in European isolates (Engh, Skrede et al, 2010; Kauserud, 2004; Kauserud et al, 2006; Maurice et al, 2014; Skrede et al, 2013). Observations of natural Agaricomycete populations indicate high numbers of MAT and vic alleles are expected due to frequency‐dependent selection acting on both loci (Coelho et al, 2017; Engh, Carlsen et al, 2010; Raper, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…To increase the resolution of genetic characterization, novel molecular markers specific for L. sulphureus were developed, using large‐scale genomic data (Nagy et al., ). SSR‐based markers are widely used and popular due to their high reproducibility and multiallelic nature , and their power for genetic characterization of populations of wood decay fungi has been demonstrated (Franzen, Vasaitis, Penttilä, & Stenlid, ; Gonthier et al., ; Maurice, Skrede, LeFloch, Barbier, & Kauserud, ; Travadon et al., ). The analysis of SSRs coupled with HRM is a robust and reproducible method (Ganopoulos, Argiriou, & Tsaftaris, ), as it has been successfully used in genotyping of plants (Distefano, Caruso, La Malfa, Gentile, & Wu, ; Xanthopoulou et al., ), and, more recently, of fungal pathogens (Sillo et al., ; Zambounis, Xanthopoulou, Karaoglanidis, Tsaftaris, & Madesis, ).…”
Section: Discussionmentioning
confidence: 99%
“…Serpula lacrymans, that has adapted to a rapid wood decay compared to its sister species, and has also gone through local adaptation within species. Serpula lacrymans in the built environment in Europe, America, Australia and New Zealand is one genetically depauperated population with only a few vegetative incompatibility types and mating type alleles (Kauserud, 2004;Kauserud et al, 2006;Maurice et al, 2014;Skrede et al, 2021). In contrast, high population diversity population is found in Japan.…”
Section: Local Adaptation In Ligninolytic Fungimentioning
confidence: 99%